2015
DOI: 10.4238/2015.november.25.12
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of accessions of Cratylia argentea (Camaratuba) using ISSR markers

Abstract: ABSTRACT. Cratylia argentea (Desv.) Kuntze (Fabaceae) is a droughttolerant, perennial legume found primarily in Brazil, Bolivia, and Peru. The shrub is well adapted to acid soils and exhibits high productivity and nutritional value, characteristics that would favor its use as a dry season animal forage supplement in semiarid regions. In plant improvement programs, the production of elite hybrids with superior traits is generally achieved by crossing parents that exhibit the highest level of genetic divergence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…The NPL is used to evaluate the efficiency of primers in dissecting the GD among individuals of accessions (Luz et al 2015) and this is consistent with our study that generated high NPL with ISST (524) and SCoT (567). Interestingly, both markers produced high PPL varying from 91.21 to 100%, with SCoT demonstrating higher efficiency by possessing a higher range of PPL (96.97-100%) than ISSR (91.21-100%).…”
Section: Discussionsupporting
confidence: 86%
“…The NPL is used to evaluate the efficiency of primers in dissecting the GD among individuals of accessions (Luz et al 2015) and this is consistent with our study that generated high NPL with ISST (524) and SCoT (567). Interestingly, both markers produced high PPL varying from 91.21 to 100%, with SCoT demonstrating higher efficiency by possessing a higher range of PPL (96.97-100%) than ISSR (91.21-100%).…”
Section: Discussionsupporting
confidence: 86%
“…In a study on Musa ssp cultivars, Ying et al (2011) identified a high percentage of polymorphism (85.1%) using ISSR markers. The number of polymorphic loci is used to evaluate the efficiency of primers at estimating the genetic diversity among individuals of a population (Luz et al, 2015). When compared with other molecular markers, ISSRs may be more effective, revealing a high degree of polymorphism.…”
Section: Resultsmentioning
confidence: 99%
“…Another factor that may cause high genetic variability in this species is the pollination mechanism it possesses, which reduces the loss of pollen, prevents autogamy, and favors cross-pollination (Darrault and Schlindwein, 2005). Luz et al (2015) concluded that ISSR markers are effective in detecting genetic variability among Cratylia argentea (Desv.) Kuntze accessions.…”
Section: Resultsmentioning
confidence: 99%